Respuesta :

Answer:

6, 10 and 8

Step-by-step explanation:

Given the recursive function an = an-1-(an-2 - 4), when a5 =-2 and a6 = 0?

a6 = a5 - (a4 - 4)

0 = -2  - (14 - 4)

2 = - (a4 - 4)

-2 = a4 - 4

a4 = -2 + 4

a4 = 2

a5 = a4 - (a3 - 4)

-2 = 2  - (a3 - 4)

-2-2 = - (a3 - 4)

-4 = -(a3 - 4)

4 = a3 - 4

a3 = 4+4

a3 = 8

Also

a4 = a3 - (a2 - 4)

2 = 8 - (a2 - 4)

2-8 = - (a2 - 4)

-6 = -(a2 - 4)

6 = a2 - 4

a2 = 6+4

a2 = 10

a3 = a2 - (a1 - 4)

8 = 10 - (a1 - 4)

8-10 = - (a1 - 4)

-2 = -(a1 - 4)

2 = a1 - 4

a1 = 2+4

a1 = 6

Hence the first 3 terms are 6, 10 and 8

Answer:

C. 6, 10, 8

Step-by-step explanation:

i took the test